Impaired ability of Nef to counteract SERINC5 is associated with reduced plasma viremia in HIV-infected individuals - Toyoda, Mako; Kamori, Doreen; Tan, Toong Seng; Goebuchi, Kageaki; Ohashi, Jun; Carlson, Jonathan; Kawana-Tachikawa, Ai; Gatanaga, Hiroyuki; Oka, Shinichi; Pizzato, Massimo; Ueno, Takamasa (Scientific reports, 2020)
HIV-1 Nef plays an essential role in enhancing virion infectivity by antagonizing the host restriction molecule SERINC5. Because Nef is highly polymorphic due to the selective forces of host cellular immunity, we hypothesized that certain immune-escape polymorphisms may impair Nef’s ability to antagonize SERINC5 and thereby influence viral fitness in vivo . To test this hypothesis, we identified 58 Nef polymorphisms that were overrepresented in HIV-infected patients in Japan sharing the same HLA genotypes. The number of immune-associated Nef polymorphisms was inversely correlated with the plasma viral load. By breaking down the specific HLA allele-associated mutations, we found that a number of the HLA-B*51:01-associated Y120F and Q125H mutations were most significantly associated with a reduced plasma viral load. A series of biochemical experiments showed that the double mutations Y120F/Q125H, but not either single mutation, impaired Nef’s ability to antagonize SERINC5 and was associated with decreasing virion infectivity and viral replication in primary lymphocytes. In contrast, other Nef functions such as CD4, CCR5, CXCR4 and HLA class I downregulation and CD74 upregulation remained unchanged. Taken together, our results suggest that the differential ability of Nef to counteract SERINC5 by naturally occurring immune-associated mutations was associated with the plasma viral load in vivo.